Trauma systems: a global comparison - Theodore Miclau, MD; Zsolt J. Balogh, MD, PhD; Katherine R. Miclau, BA; Brian Bernstein, MD; Kodi Edson Kojima, MD, PhD; Taketo Kurozumi, MD, PhD; Ross K. Leighton, MD, PhD; Douglas W. Lundy, MD, MBA; Guy Putzeys, MD; Inger B. Schipper, MD, PhD; Wim Vandesande, MD; Marcos de Camargo Leonhardt, MD, MSc; et al. (OTA International)
Abstract. Traumatic injuries are a leading cause of global morbidity and mortality, with 40 million people permanently injured and nearly 6 million deaths every year. Approximately 90% of trauma-related deaths occur in low- and middle-income countries, and 50% of trauma-related deaths are believed to be preventable. Although effective trauma systems encompassing prehospital, hospital, and rehabilitative care are critical for improving outcomes, global documentation remains limited. This study provides a comparative analysis of trauma care systems across 8 countries—the United States, Canada, Brazil, Belgium, the Netherlands, Australia, Japan, and South Africa—spanning 5 continents. Each country's analysis includes demographic context, system organization (including prehospital, hospital, and posthospital care), clinical and systemic outcomes, and future directions. Trauma systems across countries vary significantly in the structure and regulation of trauma care, injury patterns, national data collection, and accessibility, reflecting diverse demographics and healthcare infrastructures. National trauma registries are well established in countries like the Netherlands, Japan, and Canada but are in early development stages in Brazil, South Africa, and Belgium. In some countries, such as the Netherlands and Canada, trauma from traffic collisions and falls dominates, whereas others, such as Brazil and South Africa, have higher rates of violence-related injuries like homicides. Accessibility in remote areas remains a challenge in countries with large landmasses such as Canada and Australia, where rural populations often face limited or delayed trauma care. Other countries, such as the United States and South Africa, face different challenges linked to disparities in quality of and access to care between public and private systems. Although centralization of trauma care, standardization of national trauma care systems, and investment in workforce and infrastructure are universal goals for improving outcomes, solutions tailored to each country are required to optimize trauma systems globally.